“ACOSO ESCOLAR EN LOS ESTUDIANTES DE ESCUELA DE EDUCACIÓN BÁSICA “DR. LEONIDAS GARCÍA ORTÍZ”, RIOBAMBA, PERÍODO OCTUBRE 2018 – MARZO 2019” - Quimbita Chicaiza, Kely Dayana (2019)
The purpose of this investigation was to determine bullying in students from the 10th grade in the School of Basic Education "Dr. Leonidas García Ortíz ", Riobamba, Period October 2018 - March 2019; we worked with 64 students. Bullying is the repeated abuse that can be generated to a person inside and outside of an educational institution either physically, verbally or psychologically without any reason, that affects children and teenagers. Methodologically, we worked with a quantitative approach; the research design is non-experimental; the type of research is transversal and field; the level of research is descriptive and correlational; the sample was not probabilistic and intentional. For data collection, a survey was used as a technique and the questionnaire as an instrument, which facilitated the interpretation and analysis of results; it can be shown that there is bullying in the students.